Cyclic voltammetric analysis of 2-styrylchromones: Relationship with the antioxidant activity - Gomes, Ana Sara (2008)
2-Styrylchromones (2-SC) are a chemical family of oxygen heterocyclic compounds, vinylogues of flavones (2-phenylchromones), whose occurrence in nature has been reported. Recently, several 2-SC derivatives were demonstrated to have antioxidant properties, namely, xanthine oxidase inhibition, hepatoprotection against pro-oxidant agents in cellular and non-cellular systems and scavenging activity against reactive oxygen and reactive nitrogen species (ROS and RNS). Considering these antioxidant properties, it may be hypothesised that the electrochemical redox behaviour of 2-SC contributes significantly to their activity. To test this hypothesis, the electrochemical behaviour of different 2-SC was studied, together with a number of flavonoids with well-known antioxidant activities, by cyclic voltammetry, and the results correlated to their ability to scavenge ROS and RNS. The results obtained showed that 2-SC with a catecholic B-ring have a low oxidation peak potential corresponding to the oxidation of the 30,40-OH (catechol) moiety. The compounds with a phenolic B-ring have a common peak, with oxidation potential values of about +0.4/+0.5 V versus Ag/AgCl, corresponding to the oxidation of the 40-OH. The oxidation of the hydroxyl substituents in the A-ring generated peaks of higher potentials (+0.7/+0.8 V vs Ag/AgCl). The results from the scavenging assays were in agreement with those obtained from the cyclic voltammetry, that is, higher scavenging effects corresponded to lower values of oxidation potentials, with significant correlation coefficients. The values obtained for the studied flavonoids are in accordance with the literature, and reflect their relative antioxidant activity, when compared to the studied 2-SC. Thus, in this family of compounds, oxidation potentials obtained by cyclic voltammetry seem to be applicable as a general indicator of radical scavenging activity.